Colour analysis of children's drawings of gods using computer vision - Mátyás Turós (Social Sciences and Humanities Open)
The analysis of children's drawings is an important part of the educational and psychological research toolbox, and in drawing analysis the colours of representation are valuable psychological variables. In our experimental study, we use computer vision to identify the colours of drawings of God in Catholic school children (N = 360) and compare the process and results of analysis using K-means clustering and a classification approach. Our results show that the two methods do not produce the same results. The classification approach is a simpler procedure and is more suitable for comparing the results of different studies on the same topic. The colours of the students' drawings of God are, in descending order (excluding white): acromatic, blue, orange, yellow. The percentages of colours can be used in further analysis for educational and psychological studies of the use of colour.